Democratic governance and current water resources management in the upper Rio Negro basin in Uruguay - Stuhldreher, Amalia Margarita (2023)
This article examines current challenges and opportunities for integrated, sustainable, and participatory management of water resources in the upper Rio Negro basin (Uruguay) from a democratic governance perspective. For that purpose, the article adopts a qualitative methodology using techniques such as participant observation and workshops to raise awareness about the importance of this issue among key actors and decision-makers from the basin. In a context of severe global and local dilemmas regarding the democratic performance related to natural resources management, the paper reflects critical issues regarding the integrated and participatory management of water resources and proposes possible solutions. In this regard, the “local key” of the global proposal of the Sustainable Development Goals (SDGs) and the Agenda 2030 is especially significant, inasmuch necessarily entails a multilevel approach that includes the territorial dimension of this basin.